Selected living standard indicators and the ultra poor - Halder, Shantana R. (Research and Evaluation Division, Brac, 2019)
This report aimed to give a clear picture on the nature of their vulnerability and potentiality to cope wit by analysis their non-land asset base, ownership of savings and their level of human poverty. It was estimated that 91% of the ultra poor possessed any kind of non-land assets, 62% owned any productive assets and only 19% had savings. Average value of total non-land assets was only Tk. 3,787 at current price, of them value of productive assets constituted only 26%. Results on human poverty showed that 96% of the ultra poor used tube-well water for drinking, 88% for cooking, 76% for dish washing, 39% for cloth washing and 38% for bathing. Only 14% used slab/pit latrine for defecation. Eighty percent of the adult males and females possessed minimum two pieces of ordinary cloths. Access to winter clothing and footwear for all household members were for only 12% and 30% households respectively.